Menelisik Fenomena Bullying di Pesantren - Rahman, Imas Kania; Andriana, Nesia; Syahrozak, Syahrozak (STAI Auliaurrasyidin Tembilahan, 2023)
Bullying behavior often occurs in Islamic boarding schools. Based on information from the Indonesian Child Protection Commission, bullying is the most common occurrence in school environments. The aim of this study was to describe the bullying phenomenon that occurs in Islamic boarding schools. The study was carried out using a descriptive qualitative approach with data collection methods in the form of document analysis. The findings found that bullying which usually occurs in schools also occurs in Islamic boarding schools. The situation of students living in Islamic boarding schools makes bullying more likely to occur. Bullying in Islamic boarding schools is caused by several factors, namely: lack of companions which has an impact on the effectiveness of controlling student activities, negative social environment and being a role model for other students, senior and junior culture, unclear regulations regarding bullying, and lack of training for students in prevention. and management of Islamic boarding schools. This study recommends the establishment of an anti-bullying program in Islamic boarding schools through increasing the number of supervisors, anti-bullying intervention training for Islamic boarding school supervisors, drafting anti-bullying regulations, adapting and expanding anti-bullying, facilities and planning. anti-bullying curriculum, implementing anti-bullying training for students and making students anti-bullying agents in Islamic boarding schools.